Appendix-preserving elective herniorrhaphy for de Garengeot hernia: two case reports - Hiromitsu Imataki; Hideo Miyake; Hidemasa Nagai; Yuichiro Yoshioka; Koji Shibata; Yuichi Kambara; Norihiro Yuasa (Surgical Case Reports)
Abstract Background Emergency appendectomy is often performed for de Garengeot hernia. However, in some cases, there may be a chance to perform an appendix-preserving elective surgery. Case description A 76-year-old woman presented to our hospital with complaints of a right inguinal swelling, which we diagnosed as a de Garengeot hernia using computed tomography (CT). B-mode ultrasonography (US) of the mass showed an appendix 4–6 mm in diameter with a clear wall structure; color Doppler US showed pulsatile blood flow signal in the appendiceal wall. Twenty-eight days later, herniorrhaphy with transabdominal preperitoneal repair (TAPP) was performed without appendectomy. Another 70-year-old woman presented to our hospital with complaints of a painful bulge in the right inguinal region. The diagnosis of de Garengeot hernia was made using CT. B-mode US showed an appendix 5 mm in diameter with a clear wall structure. Color Doppler US showed a pulsatile blood signal in the appendiceal wall. Seven days later, herniorrhaphy with TAPP was performed without appendectomy. Conclusion De Garengeot hernia is often associated with appendicitis; however, an appendix-preserving elective herniorrhaphy can be performed if US and intraoperative findings do not suggest appendicitis or circulatory compromise in the appendix.